"Sexual dimorphism in adrenal gland development and tumorigenesis". (October 2019) - Levasseur, Adrien; Dumontet, Typhanie; Martinez, Antoine
Abstract: Sexual dimorphism not only is a matter of gonadal sex or secondary sexual characteristics but also deals with slight differences, the consequences of which may be important because, as we know, the devil is in the detail. Sex determination leads to male or female genetic programming that will influence many biological and/or pathological processes. The adrenal gland is a good example of a nonreproductive sexually dimorphic organ, and most adrenal lesions occur in females. Little is known about the mechanism behind this prevalence, but recent publications suggest the involvement of gonadal hormones and the potentially protective role of androgens. The scarcity of aggressive adrenal lesions has lead researchers to develop animal models able to recapitulate female prevalence to investigate the mechanism hidden behind this dimorphism. Males and females evolve in the same way and give rise to two not so different individuals, and in this review, we will focus on the small differences that could have deleterious effects on adrenal gland physiopathology, with a primary focus on females.